2020
DOI: 10.3390/w12092477
|View full text |Cite
|
Sign up to set email alerts
|

How to Meter Agricultural Pumping at Numerous Small-Scale Wells?—An Indirect Monitoring Method Using Electric Energy as Proxy

Abstract: The large number of users and the small scale of wells greatly complicate monitoring of groundwater abstraction in areas of intensive pumping by numerous smallholders such as in the North China Plain. This paper presents a study in a typical county in the North China Plain. It discusses the application and challenges of an indirect, energy-based approach to groundwater abstraction monitoring. Intensive field experiments at individual wells were carried out to provide a basis for the conversion from electric en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In some cases, this formula is simplified and the measured electricity is converted to the volume of pumped water using a fixed conversion factor. However, this approach is not very accurate as the conversion factor changes as a function of seasonal changes in groundwater levels and other hydrogeologic conditions (Wang et al 2020) and estimates of energy used for groundwater pumping alone can be difficult to obtain.…”
Section: Methods Of Estimating Groundwater Extraction Volumesmentioning
confidence: 99%
“…In some cases, this formula is simplified and the measured electricity is converted to the volume of pumped water using a fixed conversion factor. However, this approach is not very accurate as the conversion factor changes as a function of seasonal changes in groundwater levels and other hydrogeologic conditions (Wang et al 2020) and estimates of energy used for groundwater pumping alone can be difficult to obtain.…”
Section: Methods Of Estimating Groundwater Extraction Volumesmentioning
confidence: 99%
“…A large number of pumping tests were performed from 2016 through 2018 to determine the conversion factor between electricity consumption and pumped volume. It was shown that for a single well with a single pumping test the annual pumped volume can be estimated from the annual electricity consumed within an error of less than 20% (Wang et al 2020). The variation of the conversion factor from well to well is large with values varying between 1 m 3 /kWh and 4 m 3 /kWh for shallow wells.…”
Section: Pumping Electricity Monitoringmentioning
confidence: 99%
“…To obtain an estimate of the total annual abstraction in a village at the same accuracy, it is sufficient to apply an average conversion factor, obtained from about 20 pumping tests distributed over the village, to the aggregated annual electricity consumption of all wells involved (Wang et al 2020). In Guantao, the average conversion factors from electricity consumed to water pumped are 2.62 m 3 /kWh for shallow wells, 1.32 m 3 /kWh for deep wells and 13 m 3 /kWh for pumping of surface water from the main irrigation canal to the fields.…”
Section: Pumping Electricity Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Other indirect approaches include inverse modelling to infer extraction rates from groundwater levels (Martinez-Santos et al 2010;Shao et al 2014), remote sensing to estimate changes in groundwater storage (Castano et al 2010;Gemitzi and Lakshmi 2018;Liaqat et al 2016), agent-based modelling to link extraction rates to factors affecting human decisions (Castilla-Rho et al 2015) and statistical modelling to integrate different types of data to estimate extraction (Keir et al 2019). Indirect metering, where groundwater extraction is estimated based on energy consumption (Dash et al 1999;Frenzel 1985;Wang et al 2020) or pumping hours (Arvin 1992) is another approach that has been used to estimate groundwater extraction but requires data on extraction rates to derive extraction estimates and is most useful for mains-electricity powered wells. The primary obstacle to improving estimates of groundwater use is the general lack of metered extraction data, which is crucial in validating estimation methods and reducing uncertainty (Levin and Zarriello 2013).…”
Section: Introductionmentioning
confidence: 99%